Government Procurement Policy: Comparative Study between Indonesia and The United States - Beta Romadiyanti (Jurnal Transformative, 2022)
Public procurement is not just a process to obtain goods/services but can encourage and strengthen public policy. This study compared government procurement policies in Indonesia and the U.S. to prepare public procurement policies. This study uses a qualitative comparative method, a descriptive comparison of policies in Indonesia and the U.S. This study compares three variables: policy, organization, and human resources procurement. This study's results indicate many similarities in procurement policies in Indonesia and the U.S. Then, significant differences in the policy variables are in the details and substance of the policy in the organization. At the same time, the striking difference in the realm of the organization is the existence of a particular unit that deals with Small and/or Disadvantages businesses.